Sistem Rekomendasi Pemilihan Prioritas Surat Masuk Menggunakan Metode AHP-SAW (Study Kasus: DJBC KANWIL JATIM I) - Heryadi Mochamad Ramdani; Edy Santoso; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
DJBC KANWIL JATIM 1 is a government agency that serves the public in the field of customs and excise. Every day DJBC KANWIL JATIM1 receives letters from all sectors of the region waiting to receive orders to take action. Sometimes the regional head of office is confused about choosing which letter to take action first. Because the head of the regional office must give quick action to the letter that has the highest priority in order to get quick action. Then a letter priority recommendation system is needed that is more efficient in determining which letter is first carried out. In this study, the Analytical Hierarchy Process (AHP) and SAW (Simple Additive Weighted) methods were combined to determine the priority of incoming letters at DJAN KANWIL JATIM I. The combination of AHP and SAW methods is very well used in decision making. The AHP method is used to identify the weights for each criterion taken from the paired comparison matrix, while the SAW method is used to determine the highest priority entry letter for action. Based on the testing using the Spearman Rank Correlation Coefficient calculation produces a value of 0.86015. The results show that the system is running well.